Wybrane problemy finansowania projektów partnerstwa publiczno-prywatnego - Mataśka, Kamila (Chosen Problems of Financing Projects of Public-Private Partnership, 2009)
Public-private partnership (PPP) is becoming an ever-more frequently applied form of public task completion management. It is valued for its possibility to join public and private capitals. Properly drafted PPP contracts ensure profits for private partners (and guarantee high efficiency of accomplished public tasks, which is not the case when run by public entities) and increase commitment or private entities in the communal sector activity
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 191-198